Trend Analysis Method on Vertical Axis - Yavuz Selim GÜÇLÜ (Doğal Afetler ve Çevre Dergisi)
Climate change has accelerated with the significant increase in the amount of greenhouse gases. When the meteorological and hydrological data are examined, the effect of this change is clearly revealed. Trend test methods are frequently used to determine trends on the data. Recently, Şen-innovative trend analysis (ITA) method provides the ability to visualize inspection and identification of trend conditions. The main objective of this paper is to attempt determination and visualization of trends by means of a special graphical representation based on alternative illustration of ITA. The suggested methodology shows different trend information than classical ITA on the Mediterranean, Mediterranean-Black Sea transitional, and continental climate regions in Turkey. The vertical axis trend analysis approach proposed in this study, shows the number of data on the graph and reveals how the measurements are distributed in the high, medium and low value ranges unlike the ITA method. This research comprises 50-year rainfall records in Kırklareli, Yalova, and Alanya stations located in Turkey. The monotonic increasing trend is detected for Kırklareli data and also it is observed that the measurements are homogeneously distributed with the suggested method. In Yalova and Alanya measurements, there are non-monotonic decreasing trends and non-homogeneous distributions are determined.